Study and Characterization of Polyaniline at Various Doping of LiCl wt.% Using Electrical Measurements and XRF Analysis - Chaqmaqchee, Faten Adel Ismael; Baker, Amera Ghareeb (Journal of Research Updates in Polymer Science, 2016)
Polyaniline PANI samples were synthesized via chemical polymerization method. The mechanism of charge transport in these composites has been studies by measuring the DC conductivity at various lithium chloride LiCl wt.%. It shows that their activation energy decreases with increasing LiCl concentration and thus, the conductivity increases at 15 %wt. In addition, X-ray Fluorescence XRF was used to analysis the elements of PANI regarding to LiCl concentration. The elements positively detected by the XRF are Cl, Kr, SO3, Al2O3, SiO2, and ZrO2. The XRF data show a relative systematic error typically independent of the concentration. The accuracy is determined by comparing the XRF data with various LiCl wt.%.